Characteristics and Trends of Cutaneous Squamous Cell Carcinoma in a Patient Cohort in Finland 2006-2015 - Niina Korhonen; Leea Ylitalo; Tiina Luukkaala; Julius Itkonen; Henni Häihälä; Juha Jernman; Erna Snellman; Johanna Palve (Medical Journals Sweden, 2019)
The incidence of cutaneous squamous cell carcinoma is increasing worldwide. In most epidemiological studies, only the first case of cutaneous squamous cell carcinoma is registered, underestimating the burden of the disease. To determine the frequency and detailed characteristics of cutaneous squamous cell carcinoma in a Finnish patient cohort, we performed a retrospective 10-year study taking into account multiple tumours in one patient. On the pathology database search and medical record review we identified 774 patients with a total of 1,131 cutaneous squamous cell carcinomas. The crude incidence increased from 18.6/100,000 persons in 2006 to 28.1 in 2015. The location of tumours differed between men and women: the greatest difference concerned cutaneous squamous cell carcinoma of the ear, with 93% of cases occurring in men. One fourth (24%) of patients had more than one tumour. A small shift from poorly to well-differentiated tumours was seen. In conclusion, the incidence of cutaneous squamous cell carcinoma increased, with many patients presenting with multiple tumours.